Enterprise and Organizational Modeling and Simulation 6th International Workshop, EOMAS 2010, held at CAiSE 2010, Hammamet, Tunisia, June 7-8, 2010. Selected Papers - Barjis, Joseph; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the post-conference proceedings of the 6th International Workshop on Enterprise and Organizational Modeling and Simulation (EOMAS 2010) , held at the CAiSE 2010 conference in Hammamet, Tunisia, June 7-8, 2010. The 12 papers presented in this volume were carefully reviewed and selected from 30 submissions. They cover topics like business process management and simulation, organizational modeling and simulation, enterprise architecture and modeling, and workflow systems.
Business Process Simulation Revisited -- The Relevance of Modeling and Simulation in Enterprise and Organizational Study -- Organization Modeling and Simulation Using BORM Approach -- Agent-Based Simulation for Evaluating Flexible and Agile Business Processes: Separating Knowledge Rules, Process Rules and Information Resources -- Using Fact-Based Modeling for Business Simulation -- A Framework for the Semantic Representation of Business Processes within Business Organizational Models -- ERP Implementation Strategies: The Importance of Process Modeling and Analysis -- A Technique for Annotating EA Information Models with Goals -- Applying DEMO in Operations Research: Lot Sizing and Scheduling -- User Interfaces Modelling of Workflow Information Systems -- Mal-processes: Explicitly Modelling the Deviant -- Modeling Human Decision Behaviors for Accurate Prediction of Project Schedule Duration.
Keywords: Economics; Software engineering; Information systems; Management information systems; Economics/Management Science; Business Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl.Internet).; Software Engineering